\(\left(1+2^2+2^3+2^4+....+2^{10}\right).\left(3^2.2^4-12^2\right)\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

14 tháng 2 2018

\(\left(1+2^2+2^3+....+2^{10}\right)\cdot\left(3^2\cdot2^4-12^2\right)\)

\(=\left(1+2^2+2^3+....+2^{10}\right)\cdot\left(3^2\cdot2^{2\cdot2}-12^2\right)\)

\(=\left(1+2^2+2^3+....+2^{10}\right)\cdot\left(3^2\cdot2^2\cdot2^2-12^2\right)\)

\(=\left(1+2^2+2^3+...2^{10}\right)\cdot\left[\left(3\cdot2\cdot2\right)^2-12^2\right]\)

\(=\left(1+2^2+2^3+....+2^{10}\right)\cdot\left[12^2-12^2\right]\)

\(=\left(1+2^2+2^3+...+2^{10}\cdot0\right)\)

\(=0\)

1 tháng 8 2017

1. A = (-2)(-3) - 5.|-5| + 125.\(\left(-\dfrac{1}{5}\right)^2\)
= 6 - 25 + 125.\(\dfrac{1}{25}\)
= -19 + 5
= -14
@Shine Anna

1 tháng 8 2017

Đăng ít thôi

18 tháng 6 2019

#)Giải :

a) \(A=\frac{4^5.9^4-2^6.6^9}{2^{10}.3^8+6^8.20}=\frac{2^{10}.3^8-2^{10}.3^8.3}{2^{10}.3^8+2^8.3^8.2^2.5}=\frac{2^{10}.3^8-2^{10}.3^8.3}{2^{10}.3^8+2^{10}.3^8.5}=\frac{2^{10}.3^8\left(1-3\right)}{2^{10}.3^8\left(1+5\right)}=-\frac{1}{3}\)

\(a,A=\frac{2^{10}.3^8-2^{10}.3^9}{2^{10}.3^8+2^{10}.3^8.5}\)

\(=\frac{2^{10}.3^8\left(1-3\right)}{2^{10}.3^8\left(1+5\right)}=\frac{-1}{3}\)

Học tốt!!!!!!!!!!!!!

a) \(\frac{\left(5.2\right)}{3.2}-\frac{1}{2}x+\frac{1}{3}+\frac{1}{5}=\frac{\left(3.2\right)}{5}\)

\(\Leftrightarrow\)\(\frac{1}{2}-\frac{1}{2}x+\frac{8}{15}=\frac{6}{5}\)

\(\Leftrightarrow\)\(\frac{1}{2}-\frac{2}{3}=\frac{1}{2}x\)

\(\Leftrightarrow\)\(-\frac{1}{6}=\frac{1}{2}x\)

\(\Leftrightarrow\)x=-1/3

b) VT= \(\frac{\left(3.5.4.2\right)}{5.2.3}=4\)

\(\Leftrightarrow\left(x-\frac{1}{2}\right):6+4=4:\frac{2}{3}=6\)

\(\Leftrightarrow\left(x-\frac{1}{2}\right):6=2\)

\(\Leftrightarrow x-\frac{1}{2}=12\)

=> x= 12,5

2 tháng 4 2021

a)

4 . 25 – 12 . 25 + 170 : 10 

= (4 . 25) – (12 . 25) + (170 : 10) 

= 100 - 300 + 17 

= -183

b)

(7 + 33 + 32) . 4 – 3 

= (7 + 27 + 9) .4 – 3

= 43 . 4 – 3

= (43 . 4) – 3

= 45

c)

12 : {400 : [500 – (125 + 25 . 7)}

= 12 : {400 : [500 – (125 + 175)}

= 12 : (400: 200)

= 12 : 2

= 6

d)

168 + {[2.(24 + 32) - 2560] : 72}.

= 168 + [2 . (16 + 9) – 1] : 49

= 168 + 49: 49

= 168 + 1 

= 167

a) 

4 . 25 – 12 . 25 + 170 : 10 

= (4 . 25) – (12 . 25) + (170 : 10) 

= 100 - 300 + 17 

= -183

b)

(7 + 33 + 32) . 4 – 3 

= (7 + 27 + 9) .4 – 3

= 43 . 4 – 3

= (43 . 4) – 3

= 45

c)

12 : {400 : [500 – (125 + 25 . 7)}

= 12 : {400 : [500 – (125 + 175)}

= 12 : (400: 200)

= 12 : 2

= 6

d)

168 + {[2.(24 + 32) - 2560] : 72}.

= 168 + [2 . (16 + 9) – 1] : 49

= 168 + 49: 49

= 168 + 1 

= 167

8 tháng 2 2019

a) \(x^3-\frac{4}{25}x=0\)

\(\Leftrightarrow x\left(x+\frac{2}{5}\right)\left(x-\frac{2}{5}\right)=0\)

<=> x = 0

Xét 2 trường hợp: 

\(\Leftrightarrow x+\frac{2}{5}=0\)

      \(x=0-\frac{2}{5}\)

      \(x=-\frac{2}{5}\)

\(\Leftrightarrow x-\frac{2}{5}=0\)

      \(x=0+\frac{2}{5}\)

      \(x=\frac{2}{5}\)

\(\Rightarrow\orbr{\begin{cases}x=0\\x=\pm\frac{2}{5}\end{cases}}\)

b) \(\left(\frac{3}{8}+\frac{-3}{4}+\frac{7}{12}\right):\frac{5}{6}+\frac{1}{2}\)

\(=\left(\frac{3}{8}+\frac{-3}{4}+\frac{7}{12}\right):\frac{4}{3}\)

\(=\frac{13}{40}:\frac{4}{3}\)

\(=\frac{39}{120}=\frac{13}{40}\)

c) \(4\left(\frac{-1}{2}\right)^3-2\left(\frac{-1}{2}\right)^2+3\left(\frac{-1}{2}\right)-1\left(\frac{-1}{2}\right)^0\)

\(=4\left(\frac{-1}{2}\right)^3-2\left(\frac{-1}{2}\right)^3+3\left(\frac{-1}{2}\right)-1.1\)

\(=-\frac{1}{2}-\frac{1}{2}-\frac{3}{2}-1.1\)

\(=-\frac{5}{2}-1\)

\(=-\frac{7}{2}\)

12 tháng 9 2017

(x2-1)2=9

=> x2-1 = 3 

x2 = 3+1

x2 = 4

=> x2 = 4 = 22 ( x2=22 )

<=> x = 2

12:{390:[5.102-(53+x.72)]} = 4

390:[5.102-(53+x.72)] = 12:4

390:[5.102-(53+x.72)] = 3

5.102-(53+x.72) = 390 : 3

5.102-(53+x.72) = 130

=> 500-(125+x+49)=130

125+x+49 = 500-130

125+x+49 = 370

125+x = 370-49

125+x = 321

x = 321-125

x = 106

53(3x+2):13=103:(135:134)

53(3x+2):13=103:13

53(3x+2):13= 1000/13

125(3x+2):13 = 1000/13

125(3x+2) = 1000/13 . 13

125(3x+2) = 1000

3x+2 = 1000:125

3x+2 = 8

3x = 8-2

3x = 6

x = 6:3

x = 2